20th Annual IATUL Conference on The Future of Libraries in Human Communication, 17-21 May 1999 / [cakera padat] - Annual IATUL Conference on The Future of Libraries in Human Communication (20th : 17-21 May 1999 : Chania, Greece); International Association of Technological University Libraries (Goteborg, Sweden : IATUL Pub., 1999)
99